Smart light berbasis IoT dengan menggunakan Bylnk - Dwitama, Surya Hafidz; Elsi, Zulhipni Reno (LPPM UNIVERSITAS BINA INSAN, 2024)
Abstract The Internet of Things (IoT) has become a primary focus in the development of modern technology, including in the field of home automation. This research aims to design and implement a smart lighting control system based on IoT using the Blynk application. This system enables users to turn lights on and off remotely via a smartphone, enhancing comfort and energy efficiency.In this study, the NodeMCU ESP8266 is utilized as the microcontroller module connected to a Wi-Fi network, while a relay functions to control the electrical current to the lights. The Blynk application is installed on users' smartphones as an interface to control the system. Testing is conducted to evaluate the system's functionality, including remote control, signal stability, and energy consumption monitoring.The results show that the system operates effectively, achieving a control success rate of 96.67%. Although there are challenges related to Wi-Fi signal stability and data security, the system proves to be effective in enhancing energy usage efficiency and providing ease of control for users. This research contributes significantly to the development of smart home technology and opens opportunities for further integration with other IoT devices.